Functional taping effects on pain and electrical activation in patients with low back pain - Karolczak, Ana Paula Barcellos; Morimoto, Tissiani; Diefenthaeler, Fernando; Vaz, Marco Aurélio (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: Low back pain (LBP) is a high prevalence health problem and it has several treatments available, among them it is the functional taping. Objective: To evaluate the influence of functional taping on the electrical activation of the erector spinae muscle, the degree of pain and the functionality in subjects with LBP. Methods: Twenty female with LBP participated in the study, and were divided in two groups: with and without the use of the functional taping. The electrical activity of the erector spinae muscle was obtained bilaterally by electromyography (EMG). The root mean square (RMS) value of the EMG was calculated for three maximum voluntary contractions (MVC) obtained before and 48 hours after the application of the taping. The RMS value of each MVC was normalized by the mean RMS value of the first test for each group. The visual analog pain scale was used to measure the pain, and the Roland Morris questionnaire to evaluate the functionality. Comparisons between groups (α=5%) were performed using the Mann Whitney test, and intra-group using the Wilcoxon test. Results: There was no decrease in muscular electrical activation, a significant decrease in pain, and an improvement in functionality. Conclusion: The use of functional taping in the lumbar spine promoted positive effects related to pain and functionality.